2021
DOI: 10.1021/acsenergylett.0c02495
|View full text |Cite
|
Sign up to set email alerts
|

Organic Hole Transport Material Ionization Potential Dictates Diffusion Kinetics of Iodine Species in Halide Perovskite Devices

Abstract: Iodine-containing volatiles are major degradation products of halide perovskite materials under irradiation, yet iodine diffusion kinetics into and throughout organic hole transport materials (HTMs) and consequent reactions are largely unexplored. Here, we modify the Ca:O2 corrosion test to Ag:I2 to quantify I2 transmission rates through common organic HTMs. We observe I2 permeability to inversely correlate with HTM ionization energy, or the highest occupied molecular orbital (HOMO) energy. Tracking electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 68 publications
4
59
0
Order By: Relevance
“…As we discussed previously, postoxidation of spiro-OMeTAD by iodine gas is detrimental for the stability, especially at high temperature. This phenomena was observed in recent work by Kerner et al 84 They observed not only the oxidation of spiro-OMeTAD but also the oxidation of several organic HTL materials. They found that the HOMO levels of organic HTLs are affected by the oxidation process by iodine gases.…”
Section: ■ Challenges and Perspectivessupporting
confidence: 70%
“…As we discussed previously, postoxidation of spiro-OMeTAD by iodine gas is detrimental for the stability, especially at high temperature. This phenomena was observed in recent work by Kerner et al 84 They observed not only the oxidation of spiro-OMeTAD but also the oxidation of several organic HTL materials. They found that the HOMO levels of organic HTLs are affected by the oxidation process by iodine gases.…”
Section: ■ Challenges and Perspectivessupporting
confidence: 70%
“…We have also demonstrated that spiro‐MeOTAD can be doped by iodine sourced from I 2 vapor as well as released from the perovskite layer, resulting in increased conductivity, and displaying fast iodine/triiodide permeation rates. [ 18 ] In the device structure probed here, we exploit the ease of measuring conductivity changes in the initially undoped spiro‐MeOTAD, taking it as an indicator for iodide released from the perovskite layer. Once liberated, iodine/triiodide/iodide within the spiro‐MeOTAD is much more mobile, capable of migrating vertically and laterally to influence many observables including halide segregation.…”
Section: Resultsmentioning
confidence: 99%
“…It is due to the hydrophobic nature of the polymeric HTLs without dopants that they can protect the underlying perovskites from water. [ 60 ]…”
Section: Resultsmentioning
confidence: 99%